(untitled) (Revista de Estudios Europeos, 2026)
As part of the search for the most efficient tools possible for the cross-border collection of electronic evidence, the expected Regulation (EU) 2023/1543 was adopted on 12 July 2023, which aims to facilitate the provision and preservation of electronic evidence in criminal proceedings at European level. The Regulation is complemented by Directive (EU) 2023/1544 of 12 July 2023, which aims to establish harmonised rules for all entities operating in the territory of the European Union to be subject to the accompanying Regulation. This work attempts to critically and constructively assess the procedural repercussions of the immunities and privileges regulated therein, and which have a particular impact on the procedural guarantees of certain investigated parties by affecting the application of the delivery or preservation of electronic evidence.